2020
DOI: 10.3390/jcm9010254
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hearing Aid Use on Cognition in Older Adults: Can We Delay Decline or Even Improve Cognitive Function?

Abstract: Hearing loss is a modifiable risk factor for dementia in older adults. Whether hearing aid use can delay the onset of cognitive decline is unknown. Participants in this study (aged 62–82 years) were assessed before and 18 months after hearing aid fitting on hearing, cognitive function, speech perception, quality of life, physical activity, loneliness, isolation, mood, and medical health. At baseline, multiple linear regression showed hearing loss and age predicted significantly poorer executive function perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 73 publications
3
119
1
4
Order By: Relevance
“…Similar findings had been reported in Japan showing an approximately two‐fold increase in the odds of cognitive impairment among those who had DSI 28 . For this reason, studies had been conducted to investigate the effect of hearing aids on delaying cognitive decline and a recent study has shown a positive result 29 . It also has been demonstrated that individuals with better cognitive ability showed more aided benefit from hearing aids than those with poorer cognitive ability 30 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar findings had been reported in Japan showing an approximately two‐fold increase in the odds of cognitive impairment among those who had DSI 28 . For this reason, studies had been conducted to investigate the effect of hearing aids on delaying cognitive decline and a recent study has shown a positive result 29 . It also has been demonstrated that individuals with better cognitive ability showed more aided benefit from hearing aids than those with poorer cognitive ability 30 .…”
Section: Discussionsupporting
confidence: 73%
“…28 For this reason, studies had been conducted to investigate the effect of hearing aids on delaying cognitive decline and a recent study has shown a positive result. 29 It also has been demonstrated that individuals with better cognitive ability showed more aided benefit from hearing aids than those with poorer cognitive ability. 30 Given this finding, it is important to detect DSI early before any detrimental effect can take place.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been highlighted that subjective methods tend to overestimate HA use in comparison to datalogging (Humes et al, 2002). However, a recently published study including the participants in this study has reported reasonably high reliability between self-reported HA use and data-logging results at 18 months post HA fitting (Sarant et al, 2020).…”
Section: Study Limitationsmentioning
confidence: 52%
“…In 2017, it was estimated that the prevalence of dementia among those aged 65 or above was 9.94% and that approximately 700,000 individuals had dementia [2]. Along with the advance of pharmacological treatments or interventions, modifiable dementia risk factors need to be addressed to prevent this disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dementia is a degenerative disease, its early diagnosis is critical, and considerable effort has been invested in preventing and curing dementia [4]. To receive a diagnosis of dementia, diverse treatments or interventions, modifiable dementia risk factors need to be addressed to prevent this disease [3].…”
Section: Introductionmentioning
confidence: 99%